Experiências de Ecoturismo em Unidades de Conservação: análise de relatos de visita ao Parque Nacional de Sete Cidades (Piauí) - Johannes de Oliveira Lima Júnior; Rafael Fernandes de Mesquita; Fábio Freitas Schilling Marquesan; Adriana Kirley Santiago Monteiro; Adelquis Stanley Monteiro Santiago (Confins)
Ecotourism in Brazilian Conservation Units (UCs) is gaining increasing popularity, yet understanding visitor perceptions of its key elements remains limited. This study analyzed 208 online comments from TripAdvisor about Sete Cidades National Park (Piauí) using the IRaMuTeQ software. The findings revealed that contact with nature is the primary attraction for visitors, while environmental preservation and environmental education receive less emphasis. This research contributes to the debate on ecotourism management, highlighting the need for environmental education initiatives and investment in infrastructure to promote sustainable local development.